Dynamics of curved fronts - Pelce, Pierre, 1959- (Perspectives in physics., 1988)
In recent years, much progress has been made in the understanding of interface dynamics of various systems: hydrodynamics, crystal growth, chemical reactions, and combustion. Dynamics of Curved Fronts is an important contribution to this field and will be an indispensable reference work for researchers and graduate students in physics, applied mathematics, and chemical engineering. The book consist of a 100 page introduction by the editor and 33 seminal articles from various disciplines.